Differences in Cognitive Impairment in Primary Age-Related Tauopathy Versus Alzheimer Disease. Issue 3 (1st February 2019) - Besser, Lilah M; Mock, Charles; Teylan, Merilee A; Hassenstab, Jason; Kukull, Walter A; Crary, John F
Abstract: This study examined differences in neuropsychological test scores between individuals with primary age-related tauopathy (PART) and Alzheimer disease (AD) using cross-sectional data from the National Alzheimer's Coordinating Center. Linear regression tested for differences in 4 cognitive domains stratified by cognitive status (global Clinical Dementia Rating [CDR]). The sample included 240 participants with no neuritic plaques (NP) (definite PART), 186 with sparse NP (possible PART), and 510 with moderate/frequent NP (AD). Four cognitive domain z -score outcome variables (memory, attention, executive function, and semantic memory/language) were calculated using 12 neuropsychological tests. Definite PART participants had a sparing of semantic memory/language compared to those with AD, with a mean adjusted z -score difference of 0.37 (95% confidence interval [CI]: 0.16–0.58) for those with CDR = 0.5 or 1 and of 0.92 (CI: 0.22–1.63) for those with CDR = 2 or 3. Compared to participants with AD, definite PART participants with CDR = 0.5 or 1 had sparing of memory (adjusted z -score difference: 0.61; CI: 0.39–0.84) and definite PART participants with CDR = 2 or 3 had sparing of attention (adjusted z -score difference: 0.76: CI: 0.09–1.43). Patterns of cognitive impairment differed between definite PART and AD, suggesting significant differences in clinical presentation between individuals from these 2 groups.